2006
DOI: 10.1007/s11062-006-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected effect of capsaicin on spontaneous GABA-ergic IPSCS in hippocampal cell cultures

Abstract: Vanilloid receptors 1 (VRs1) expressed in a subpopulation of sensory neurons and responsible for processing of chemical and thermal noxious stimuli were also shown to be expressed in several cerebral structures and to be involved in the regulation of glutamatergic synaptic transmission. In this study, we started to investigate the possibility that VRs1 are also involved in the regulation of GABA-ergic synaptic transmission. For this purpose, the effect of a VR1 agonist, capsaicin, on spontaneous GABA-ergic inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Similarly, capsaicin along with Triton X‐100, octyl‐β‐glucoside, and docosahexaenoic acid directly inhibits human α1β2γ2S GABA A subunits expressed in HEK293 cells 168 through changes in lipid bilayer elasticity. In line with these findings, using patch‐clamp technique, it was found that capsaicin (10 μM) decreased both the frequency and amplitude of spontaneous inhibitory post‐synaptic currents in hippocampal cell cultures 169 …”
Section: Effects Of Capsaicinoids On Ligand‐gated Ion Channelssupporting
confidence: 63%
See 1 more Smart Citation
“…Similarly, capsaicin along with Triton X‐100, octyl‐β‐glucoside, and docosahexaenoic acid directly inhibits human α1β2γ2S GABA A subunits expressed in HEK293 cells 168 through changes in lipid bilayer elasticity. In line with these findings, using patch‐clamp technique, it was found that capsaicin (10 μM) decreased both the frequency and amplitude of spontaneous inhibitory post‐synaptic currents in hippocampal cell cultures 169 …”
Section: Effects Of Capsaicinoids On Ligand‐gated Ion Channelssupporting
confidence: 63%
“…In line with these findings, using patch-clamp technique, it was found that capsaicin (10 μM) decreased both the frequency and amplitude of spontaneous inhibitory post-synaptic currents in hippocampal cell cultures. 169 The nACh receptor, which is a cation channel and the prototype for ligand-gated ion channels, has also been reported to be inhibited by capsazepine (10 µM) in rat trigeminal neurons. 170 In addition to capsazepine, capsaicin has also been shown to modulate the function of nicotinic receptors.…”
Section: Effects Of Capsaicinoids On Ligand-gated Ion Channelsmentioning
confidence: 99%
“…10 To elaborate, the TRPV1 channel modulates glutamatergic and GABAergic transmission and causes changes in neuronal firing. 25,26 Thus, it has a role in brain plasticity and development. 10, 27 Moreover, numerous studies have shown that the TRPV1 channel is implicated in the regulation of long-term potentiation of excitatory postsynaptic potentials in the hippocampus which is responsible for learning and memory.…”
Section: Trpv1 In Healthmentioning
confidence: 99%
“…In addition to modulation of glutamatergic transmission, TRPV1 can be also involved in the modulation of GABAergic transmission [39]. For instance, TRPV1 activation by capsaicin or by the endocannabinoid anandamide depresses somatic, but not dendritic inhibitory GABAergic transmission in both rat and mouse dentate gyrus [40].…”
Section: Trpv1 In the Brainmentioning
confidence: 99%